Glenohumeral and hip range-of-motion and strength measures in youth baseball athletes - Picha, K. J.; Harding, J. L.; Huxel Bliven, K. C. (Journal of Athletic Training, 2016)
Context: The repetitive demands of throwing affect glenohumeral (GH) range of motion (ROM) and strength. Less is known about hip alterations in skeletally immature athletes.